2011
DOI: 10.1159/000323035
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Start during Continuous Renal Replacement Therapy in Vasopressor-Dependent Patients: The Impact of a Slow Blood Flow Protocol

Abstract: Background and Aims: In vasopressor-dependent patients, we evaluated the impact of a slow blood flow protocol on hypotension when starting continuous renal replacement therapy (CRRT). Methods: Retrospective observational study in tertiary ICU of a slow blood flow protocol at the start of CRRT circuits. Results: 205 circuits in 52 patients were studied. No significant changes in mean arterial pressure (MAP) and norepinephrine dose were found. Only 16 circuit starts in 13 patients were associated with a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Patients at higher risk of complications, given hemodynamic instability at baseline, are more likely to be selected for treatment with CRRT (or SLED). Hypotension at CRRT initiation has been reported in 18.8–25.0% of patients [ 8 , 54 ]. Kim et al [ 54 ] also assessed hypotension in relation to CRRT initiation and found that it affected 7.8% of circuit starts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients at higher risk of complications, given hemodynamic instability at baseline, are more likely to be selected for treatment with CRRT (or SLED). Hypotension at CRRT initiation has been reported in 18.8–25.0% of patients [ 8 , 54 ]. Kim et al [ 54 ] also assessed hypotension in relation to CRRT initiation and found that it affected 7.8% of circuit starts.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension at CRRT initiation has been reported in 18.8–25.0% of patients [ 8 , 54 ]. Kim et al [ 54 ] also assessed hypotension in relation to CRRT initiation and found that it affected 7.8% of circuit starts. Eastwood et al [ 18 ] compared CRRT routine and slow blood flow rates at initiation and reported no hypotensive events in either arm.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, that same group [ 2 ] published a retrospective study to analyze the impact of the slow blood flow protocol in vasopressor-dependent patients. They studied 205 circuit connections and a decrease in MAP > 20% was only observed in 16 out of 205 connections (7.8%) and CRRT did not have to be discontinued because of hypotension in any patient.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous renal replacement therapy (CRRT) is most commonly used in this setting, since it is better tolerated than intermittent therapy from a hemodynamic point of view. Nevertheless, hypotension during and after the connection to CRRT is very common [ 2 , 3 ]. In adult patients, hemodynamic instability during CRRT is associated with changes in circulating blood volume, blood flow rate variability, and electrolyte disturbances [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we performed a retrospective observational study to evaluate the impact of a CRRT start safety protocol in critically ill vasopressor-dependent AKI patients [10]. We found that less than 2% of circuit starts (n = 500) were associated with hypotension (defined as a decrease of 20% from baseline mean arterial pressure (MAP) and that even in high-risk patients (noradrenaline rate greater than 50 µg/min) only a minority had experienced hypotension (defined as a MAP <50 mm Hg).…”
Section: Introductionmentioning
confidence: 99%